Relational Maintenance Strategies During the Post Sex Time Interval. Issue 3 (27th May 2017) - Denes, Amanda; Dhillon, Anuraj; Speer, Annika C.
Abstract : The present study contributes to a growing line of research exploring the role of post sex communication in building and sustaining romantic relationships. More specifically, this study explores the use of relational maintenance strategies during the post sex time interval (PSTI). One-hundred and fifty-two individuals completed surveys after sexual activity and indicated the relational maintenance strategies they enacted during the PSTI. Results revealed that individuals enact the strategies of positivity and assurances to the greatest degree during the PSTI. Furthermore, extending the post sex disclosures model, results revealed that orgasm predicted differences in the use of assurances during the PSTI and that the strategy of assurances mediated the association between orgasm and several relationship outcomes (i.e., liking, commitment, control mutuality, and satisfaction). These findings suggest that individuals may use the PSTI as a time to reinforce their commitments to their partners, and that such behavior is associated with characteristics of the sexual episode and relationship outcomes. The implications of these findings for research on relational maintenance and post sex behavior are discussed.